No Evidence That Substance Use Causes ADHD Symptoms in Adolescence. (July 2017) - Murray, Aja Louise; Eisner, Manuel; Obsuth, Ingrid; Ribeaud, Denis
There is a robust association between attention-deficit hyperactivity disorder (ADHD) symptoms and elevated substance use. Several plausible causal pathways from ADHD to substance use have been articulated and supported empirically. In this study, we tested the recent suggestion that substance use could also influence levels of ADHD symptoms. Using the three most recent waves of data from the Zurich Project on the Social Development of Children and Youth (z-proso), we found significant and strong cross-lagged effects of ADHD symptoms on substance use but no significant effects in the opposite direction. This suggests that individual differences in substance use are not related to increases in ADHD symptoms in adolescence. Adolescent-onset symptoms of ADHD are thus unlikely to be caused by substance use, and targeting substance use problems is unlikely to reduce ADHD symptoms.